Pengaruh Rasio Arus Kas, Likuiditas, Profitabilitas Terhadap Kondisi Financial Distress Perusahaan - Anggraeni Putri, Dista Dwi; Tumirin (Journal of Culture Accounting and Auditing, 2025)
This research aims to test financial distress with predictors of cash flow, profitability, liquidity on the company's financial distress condition. This research uses 51 samples of company financial reports to analyze the condition of companies listed on the Indonesia Stock Exchange (BEI). This research data is secondary data obtained on the Indonesia Stock Exchange (BEI). Secondary data is data that already exists and does not need researchers to collect it themselves. The data required by researchers is the financial reports of food and beverage sector companies. This type of research is quantitative research. This research uses a purposive sampling method. Testing was carried out using logistic regression. This research uses IBM SPSS Statistics 22 to test the variables studied. The research results show that profitability is significantly related to financial difficulties. Meanwhile, the cash flow ratio and liquidity ratio are not significantly related to financial distress.